Study of the Use of Accounting Information at BUMDES in Pematang Serai Village, Langkat Regency - Galih Supraja; Mustafa Mustafa; Farah Soufika Thahirah (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to analyze the model of using accounting information at BUMDES in Pematang Serai Village, Langkat Regency in order to increase Village Original Income through accounting training, length of business establishment and business scale in using the BUMDES accounting information system in Pematang Serai Village, Langkat Regency by collecting data using a questionnaire . The tests used in this study were data quality tests, data normality tests, multiple linear regression analysis, and hypothesis testing. The regression model used in this study is a multiple linear regression model with the help of statistical test tools. The sampling method in this study used the Random Sampling method (random) which obtained as many as 30 BUMDES managers in Pematang Serai Village, Langkat Regency. Regression test results The first hypothesis is accepted and H0 is rejected, where the results of the T test on the accounting training variable obtain a probability of Sig. By 0.000. which means the Sig value ≤ 0.05 or (0.000 ≤ 0.05), as well as the T value calculated in accounting training is 8.681 . And the T table value is 2.0518 so that a value can be obtained (Tcount ≥ Ttable) or (8.691 ≥ 2.0518). because accounting training has a significant effect on the use of accounting information systems at BUMDES in Pematang Serai Village, Langkat Regency. The results of the second hypothesis regression test were rejected and H0 was accepted where the results of the T test on the long standing business variable obtained a sig probability of 0.329. Which means the sig value > 0.05 or (0.329 > 0.05). Likewise with the value of Tcount -0.995 . And the Ttable value is 2.0518. So that the value (Tcount <Ttable) or (-0.995 <2.0518) can be obtained, which means that the long standing variable has no significant effect on the use of accounting information systems at BUMDES in Pematang Serai Village, Langkat Regency. The results of the third hypothesis regression test were rejected and H0 was accepted where the results of the T test on the business scale variable obtained a sig probability of 0.586. Which means the sig value > 0.05 or (0.586 > 0.05), . Likewise with the calculated T value of 0.551 . And the T table value is 2.0518 . So that a value can be obtained (T count < T table) or (0.55551 < 2.0518). which means that the business scale variable has no significant effect on the use of the accounting information system at BUMDES in Pematang Serai Village, Langkat Regency.